LANDSCAPE AND RECREATIONAL CAPACITY OF THE TERRITORY OF CAUCASUS MINERALNYE VODY REGION FOR TOURISM DEVELOPMENT - V. S. Proskurin (Наука. Инновации. Технологии)
Introduction: The Region of Caucasus Mineralnye Vody region has the various landscape and recreational potential for development of medical, mountain and sports and tourist and excursion activity. A basis of a research is landscape approach which acts as all-methodological base in justification of zoning of the territory for different types of tourism, assessment of with-tsilno-economic functions reflecting extent of possible participation of a landscape in satisfaction of recreational requirements of society. Results of a research allow to distinguish sites of potential development of separate types of tourism taking into account integrated assessment. Materials and methods: complex assessment of landscape and recreational capacity of the territory, includes the analysis of components of a landscape: relief and raschlenennost of the territory, climate, hydrography, landscape biotics. The technique of identiication of zones with the largest landscape and recreational potential for development of tourism means creation of hexagonal operators with the party of 5 km and calculation in grounds (cells) of the selected indicators in QGIS geographic information system. After calculation for each ground classiication of components by a 5-ball scale on the basis of an algorithm of natural borders Dzhenkens was carried out. The algorithm means natural group of data. Borders of classes are deined so that to group similar values and as much as possible to increase differences between classes for visual identification of zones. Results of researches and discussion: The main result of work - complex assessment of components of a landscape in relation to various directions of tourism. This assessment allows to carry out zoning of the territory according to the obtained data. At the same time it is important that for each type of tourism the deining value was accepted by that component of a landscape which has the largest weight. Results of a research are used when developing the master plan of the city district of the resort town of Kislovodsk, and further can be used when developing documents of strategic and territorial planning. Conclusions: The received landscape and recreational zoning allows to allocate landscapes with the largest potential for separate types of tourism. So, for extreme tourism the most perspective zone of development is the cultural and natural landscape the kuestovykh of ridges and also local sites of a landscape alluvial the terrasirovannykh of valleys. The greatest indicators for development of ecological tourism were received by the area in the west of the foothills the ostepnennykh of meadows and meadow steppes. The least favorable for development of all presented types of tourism landscapes the degressionnykh of the opened lands and also landscapes of eroziono-accumulative plains possess. This integrated and strategic approach shows territories with the largest potential of development.